Mcl-1 protects eosinophils from apoptosis and exacerbates allergic airway inflammation. Issue 7 (17th April 2020) - Felton, Jennifer M; Dorward, David A; Cartwright, Jennifer A; Potey, Philippe MD; Robb, Calum T; Gui, Jingang; Craig, Ruth W; Schwarze, Jürgen; Haslett, Christopher; Duffin, Rodger; Dransfield, Ian; Lucas, Christopher D; et al.
Abstract : Eosinophils are key effector cells in allergic diseases. Here we investigated Mcl-1 (an anti-apoptotic protein) in experimental allergic airway inflammation using transgenic overexpressing human Mcl-1 mice (hMcl-1) and reducing Mcl-1 by a cyclin-dependent kinase inhibitor. Overexpression of Mcl-1 exacerbated allergic airway inflammation, with increased bronchoalveolar lavage fluid cellularity, eosinophil numbers and total protein, and an increase in airway mucus production. Eosinophil apoptosis was suppressed by Mcl-1 overexpression, with this resistance to apoptosis attenuated by cyclin-dependent kinase inhibition which also rescued Mcl-1-exacerbated allergic airway inflammation. We propose that targeting Mcl-1 may be beneficial in treatment of allergic airway disease.